Translation of Charles, Ifeanyi, Uche and Joe Oloko - Oloko, Patrick; Kibora, Ludovic (Rethinking the "Informal" and Mainstreaming African Popular Arts and Entertainment, 2021)
Translation of interview with Charles, Ifeanyi, Uche and Joe Oloko of Rethinking the Informal and Mainstreaming African Popular Arts and Entertainment
Keywords: Arts; Aesthetics; Music; Scholars; African Studies; Popular Music Studies; African Music; Cultural Economy